2021
DOI: 10.1186/s12959-021-00334-2
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumor is the greatest risk factor for pulmonary embolism in hospitalized patients: a single-center study

Abstract: Background This study aimed to investigate the background of patients who presented with pulmonary embolism (PE) on contrast-enhanced chest computed tomography (CT) and to explore the risk factors for PE. Methods This study included a review of the medical records of all 50,621 patients who were admitted to one community hospital between January 1, 2013 and December 31, 2017. Data on sex, age, risk factors related to blood flow stagnation (obesity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Besides the well-established risk factors for PE including advanced age, obesity, long-time bed rest, prolonged operation times, malignant tumor is the greatest risk factor for PE in hospitalized patients according to the literature [9]. Furthermore, malignancy-related risk factors such as cancer type, cancer stage and primary site have been documented to be associated with VTE and PE in cancer patients [10,11].…”
mentioning
confidence: 99%
“…Besides the well-established risk factors for PE including advanced age, obesity, long-time bed rest, prolonged operation times, malignant tumor is the greatest risk factor for PE in hospitalized patients according to the literature [9]. Furthermore, malignancy-related risk factors such as cancer type, cancer stage and primary site have been documented to be associated with VTE and PE in cancer patients [10,11].…”
mentioning
confidence: 99%
“…Moreover, obesity and hypertension were found to be independently associated with PE, while age (Model 2, P = 0.052) and sex (Model 2, P = 0.075) were close to achieving statistical significance. Indeed, age, sex and obesity have already clearly been identified as risk factors for PE ( 40 ). Interestingly, the adjusted ORs of hypertension were less than 1.0, implying that hypertension appeared to be a protective factor for PE, which seems controversial with clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer has long been recognized as an important risk factor for PE ( 28 , 40 ). In this study, patients with PE had a higher proportion of cancer than those without (20.54% vs. 14.42%), and univariate analysis showed that patients with cancer had a 1.535-fold increase in PE risk ( P = 0.026).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 3.1 million new cases are diagnosed in China every year, and this number has been increasing each year 18 , 19 . Depending on the severity of the embolism, both symptomatic and asymptomatic embolism can occur 20 , 21 . Acute SPE is a condition we must be on high alert for because it may be life-threatening 9 .…”
Section: Discussionmentioning
confidence: 99%